Vedic nouns of the rétas- ‘stream; semen’ type and several related problems of Indo-European morphology - Vijūnas, Aurelijus (Acta Orientalia Vilnensia, 2008)
National Kaohsiung Normal UniversityThe present article is dedicated to the historical analysis of the formant -t- appearing in the Sanskrit neuter s-stem nouns srótas- ‘stream’, rétas- ‘stream; (male) semen’, and †vétas- ‘reed; stick’, as well as the structure and derivation of these nouns. Already Hermann Hirt already proposed that the formant -t- in these nouns was related to the Indo-European t-stems, but alternative interpretations have been put forward as well. Among the existing theories regarding the origin of the formant -t- in these s-stems, Hirt’s theory appears to be the most plausible. A different interpretation regarding the structure and development of their root is proposed in this article, however. Hirt claimed that the normal grade of the root in these nouns was inherited from Indo-European, but an analysis of data suggests that late Indo-European t-stems built to roots of this structure must have had zero grade. The attested full grade must have been introduced only when the reformed roots *srut-, *rit- and *wit- (← **R-t-) were secondarily re-used to build new s-stem nouns.